IdeAR: Augmented Reality Applied to Reading Comprehension Stories - Pretell Cruzado, Johny (2020)
A problem in many schools is the difficulty of students to understand texts, which is due to multiple factors, including habits and motivation to read. On the other hand, augmented reality is a didactic technology which, when applied to the educational area, becomes a dynamic, interactive activity and arouses interest in the student. This study shows the results obtained after the application of augmented reality for reading comprehension through stories in fourth grade primary students. A mobile application based on augmented reality named “IdeAR” was implemented using Mobile-D methodology. For empirical demonstration the statistical sample included two sections of students from a public school in Lima city, where the experimental group showed improvements in memory level and content understanding. Finally, this work is important for the educational sector because it provides a tool that favors teaching with a STEAM approach.